Electrocatalytic Hydrogenation of N(2) to NH(3) by MnO: Experimental and Theoretical Investigations - Wang, Zao (Adv Sci (Weinh), 2018)
NH(3) is a valuable chemical with a wide range of applications, but the conventional Haber–Bosch process for industrial‐scale NH(3) production is highly energy‐intensive with serious greenhouse gas emission. Electrochemical reduction offers an environmentally benign and sustainable route to convert N(2) to NH(3) at ambient conditions, but its efficiency depends greatly on identifying earth‐abundant catalysts with high activity for the N(2) reduction reaction. Here, it is reported that MnO particles act as a highly active catalyst for electrocatalytic hydrogenation of N(2) to NH(3) with excellent selectivity. In 0.1 m Na(2)SO(4), this catalyst achieves a high Faradaic efficiency up to 8.02% and a NH(3) yield of 1.11 × 10(−10) mol s(−1) cm(−2) at −0.39 V versus reversible hydrogen electrode, with great electrochemical and structural stability. On the basis of density functional theory calculations, MnO (200) surface has a smaller adsorption energy toward N than that of H with the *N(2) → *N(2)H transformation being the potential‐determining step in the nitrogen reduction reaction.